The status of bovine brucellosis in Gauteng Province, South Africa, 2020 - Liesl De Boni; Adri Grobler; Duma Mpofu; Jaison Mpofu; Peter Geertsma (Journal of Interventional Epidemiology and Public Health)
Introduction: A population-based survey was carried out to estimate the prevalence of bovine brucellosis in an endemic area (Gauteng Province, South Africa) and to study possible risk factors.